2014
DOI: 10.1007/s10964-014-0176-x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Electronic Media Use at Night, Sleep Disturbance, and Depressive Symptoms in the Smartphone Age

Abstract: Adolescence is a time of increasing vulnerability for poor mental health, including depression. Sleep disturbance is an important risk factor for the development of depression during adolescence. Excessive electronic media use at night is a risk factor for both adolescents' sleep disturbance and depression. To better understand the interplay between sleep, depressive symptoms, and electronic media use at night, this study examined changes in adolescents' electronic media use at night and sleep associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
452
9
23

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 715 publications
(562 citation statements)
references
References 55 publications
36
452
9
23
Order By: Relevance
“…Present study found strong correlation between smart phone over usage and prevalence of depression, anxiety and stress, which is not consistent with results of previous study conducted by Lemola et al, did not find any relationship between smartphone ownership and symptoms of depression. 15 However, Hwang et al found that state anxiety, trait anxiety, and depression were higher in the smartphone overuse group than in the normal use group among college students which is similar to results of this study. 16 Present findings on depression and anxiety are highly consistent with those of previous studies.…”
Section: -11supporting
confidence: 89%
“…Present study found strong correlation between smart phone over usage and prevalence of depression, anxiety and stress, which is not consistent with results of previous study conducted by Lemola et al, did not find any relationship between smartphone ownership and symptoms of depression. 15 However, Hwang et al found that state anxiety, trait anxiety, and depression were higher in the smartphone overuse group than in the normal use group among college students which is similar to results of this study. 16 Present findings on depression and anxiety are highly consistent with those of previous studies.…”
Section: -11supporting
confidence: 89%
“…Lemola et al reported that smartphone ownership was related to late bedtimes in adolescents but it was unrelated to sleep disturbance. 22 Various studies have reported that the addiction or overuse of electronic devices, Internet and smartphone are similar as for as their effect on sleep is concerned as they lead to exposure to either bright light of the screens or electromagnetic radiations or both.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, Lemola et al (2015) found electronic media use before bed to be associated with teens' depressive symptoms, with reduced sleep duration accounting for this association. Although the cross-sectional design precludes making causal inferences, these findings nonetheless point to the importance of considering adolescent-salient contextual factors when examining the concurrent and longitudinal link between sleep and depression.…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 96%